Computationally Efficient Implicit ADI Theory and Its Open Region Problems for Anisotropic Gyrotropic Plasma Simulations. Issue 11 (4th October 2020) - Wu, Peiyu; Xie, Yongjun; Jiang, Haolin; Natsuki, Toshiaki
Abstract: With its unique anisotropic characteristic, gyrotropic plasma is extensively employed in a series of applications. As it is hard to obtain the electric behavior of anisotropic gyrotropic plasma directly, numerical simulation is regarded as one of the most important ways on the investigation. Based upon higher order formulation and an alternating‐direction‐implicit (ADI) procedure, the unconditionally stable ADI perfectly matched layer (PML) is proposed in finite‐difference time‐domain lattice to solving the open region problems for anisotropic gyrotropic plasma. To decouple the updated equations in the gyrotropic plasma regions, approximate decoupling theory is introduced during the implementations. The proposed implementation takes advantages of the higher order formulation, ADI procedure, approximate decoupling theory, and PML implementation in terms of considerable absorption, efficiency, and accuracy in open region problems. Numerical examples are carried out for the demonstration of effectiveness both in theory and experimentally. Through the results, it can be concluded that the proposed implementation is effective and accurate for terminating anisotropic gyrotropic plasma in open region problems when time step surpasses far beyond the Courant–Friedrich–Levy condition. Abstract : Based upon higher order formulation and an alternating‐direction‐implicit (ADI) procedure, unconditionally stable ADI perfectly matched layer (PML) is proposed in finite‐difference time‐domain lattice for anisotropic gyrotropic plasma. To decouple the updated equations, approximate decoupling theory is introduced. The proposed implementation takes advantages of the higher order formulation, ADI procedure, approximate decoupling theory, and PML implementation in terms of considerable absorption, efficiency, and accuracy.